Stress-specific changes of galanin and PACAP expression in the rat hypothalamus and adrenal gland - Lakić, Iva; Jevđović, Tanja; Jasnić, Nebojša; Dakić, Tamara; Vujović, Predrag; Đorđević, Jelena (Archives of Biological Sciences, 2018)
Paper dfescription: Neuropeptides galanin and pituitary adenylate cyclase-activating peptide (PACAP) play an important role in mediating the stress response. We showed for the first time that galanin and PACAP displayed specific responses which depended on the duration and type of stressor, with hypothalamic and adrenal expression of galanin and PACAP mRNA increased after repeated restraint and acute immobilization, respectively. Unlike PACAP which remained unchanged, the hypothalamic galanin content increased regardless of the type and duration of applied stressor. Both galanin and PACAP levels remained unaffected by the stressors in the adrenal gland. Abstract: Galanin and pituitary adenylate cyclase-activating peptide (PACAP) are involved in the stress response, and both produce multiple effects in the central and peripheral nervous systems. In rodents, galanin brain expression is altered by different stressors, while PACAP has a critical role in the circuits mediating the stress-response. The aim of this study was to investigate whether acute and/or repeated immobilization (IMO) and restraint (R) differently affect galanin and PACAP expression in the rat hypothalamus and adrenal gland. Relative expression of mRNAs was examined by qPCR and relative changes in the protein content were analyzed using Western blotting. The distribution of galanin and PACAP peptides in the hypothalamus was analyzed by immunofluorescence. Relative hypothalamic expression of both galanin and PACAP mRNAs was increased only after repeated restraint. Hypothalamic galanin protein levels were increased after all applied stressors, whereas there were no changes in the PACAP content. In the adrenal glands, galanin and PACAP mRNAs were elevated only after acute IMO, whereas the protein levels were not changed, regardless of the applied stressor or its duration. Immunofluorescence staining demonstrated the presence of galanin in the paraventricular nuclei (PVN) of the hypothalamus in all groups. Galanin immunoreactivity was stronger in the PVN of all stressed groups in comparison to the control. We concluded that the patterns of transcriptional activation and translational control of galanin and PACAP in the examined tissues depended on the type (IMO vs. R) and duration (acute vs. repeated) of the applied stressor. https://doi.org/10.2298/ABS180228008L Received: February 28, 2018; Revised: March 13, 2018; Accepted: March 13, 2018; Published online: March 21, 2018 How to cite this article: Lakić I, Jevđović T, Jasnić N, Dakić T, Vujović P, Đorđević J. Stress-specific changes of galanin and PACAP expression in the rat hypothalamus and adrenal gland. Arch Biol Sci. 2018;70(3):…